Ultrastructural feature of spermatogenic cells and spermatozoon in cultured burbot Lota lota - Dadras, Hadiseh; Golpour, Amin; Dzyuba, Borys; Kristan, Jiri; Policar, Tomas (Tissue & cell, 2019)
Testis development and ultrastructure of spermatogenic cells and spermatozoa of burbot Lota lota, a commercially important cold freshwater fish, were studied by light and transmission electron microscopy. Spermatogonia, spermatocytes, spermatids, and spermatozoa are distributed along the seminiferous tubules. Electron-dense bodies appear in germ cells from primary spermatogonia to secondary spermatocytes. We identified three distinct stages of spermatid cell differentiation based on chromatin condensation, development of the flagellum, formation of a nuclear fossa, and elimination of excess cytoplasm. Spermatozoa were anacrosomal and characterized by location of the centrioles outside the nuclear fossa and incomplete perpendicular arrangement of the centrioles. The sperm flagellum displayed an axoneme with nine doublets of peripheral microtubules and two central microtubules. These results provide valuable information for burbot taxonomy and may clarify the process of spermatogenesis for this species.
Keywords: Spermatogenic cells; Electron microscopy; spermatogonie; Male; Spermatids; spermatogeneze; Spermatozoa; Sertoli Cells; Spermatogenesis; mužské pohlaví; Testis; ryby; Spermatogonia; Fishes; kultivované buňky; Animals; zvířata; testis; Sertoliho buňky; spermatidy; spermie; Cells, Cultured; Testis ultrastructure